LIVING THE TEMPLE AS EXPRESSION OF CHINESE PHILOSOPHY AND CULTURE - Ardian Cangianto (Bambuti, 2021)
The temple is not always defined as a mere place of worship but also has multiple functions and cannot stand alone without any connection with others. This paper intends to provide an understanding of the temple as a form of expression of Chinese philosophy and culture. When gender becomes a problem in society, temples can also provide a way out, containing many social elements that are forgotten. Competition for the temple to be claimed by religious institutions makes the temple even more ambiguous and confusing. Such actions further alienated the temple from the development of the times and also lost social values ​​that were horizontal